2014
DOI: 10.1186/s12888-014-0216-9
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders in Bangladesh: a systematic review

Abstract: BackgroundMental disorders constitute a major public health problem globally with higher burden in low and middle-income countries. In Bangladesh, systematically-collected data on mental disorders are scarce and this leaves the extent of the problem not so well defined. We reviewed the literature on mental health disorders in Bangladesh to summarize the available data and identify evidence gaps.MethodsWe identified relevant literature on mental disorders within Bangladesh published between 1975 and October, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
199
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(209 citation statements)
references
References 30 publications
7
199
2
1
Order By: Relevance
“…Still, it is widely acknowledged, that mental disorders constitute an important and neglected problem in these countries, putting a high and often life-long burden on people living with it [1]. Only a limited number of studies were performed with regard to the prevalence of mental health disorders in Bangladesh, which were summarized in a recent review by [2]. The results showed that prevalence rates of mental disorders (most commonly depression and anxiety) varied from 6.5 to 31% in adults and from 13.4 to 22.9% in children and adolescents [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is widely acknowledged, that mental disorders constitute an important and neglected problem in these countries, putting a high and often life-long burden on people living with it [1]. Only a limited number of studies were performed with regard to the prevalence of mental health disorders in Bangladesh, which were summarized in a recent review by [2]. The results showed that prevalence rates of mental disorders (most commonly depression and anxiety) varied from 6.5 to 31% in adults and from 13.4 to 22.9% in children and adolescents [2].…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of studies were performed with regard to the prevalence of mental health disorders in Bangladesh, which were summarized in a recent review by [2]. The results showed that prevalence rates of mental disorders (most commonly depression and anxiety) varied from 6.5 to 31% in adults and from 13.4 to 22.9% in children and adolescents [2]. Underreporting and underdiagnosis, however, were assumed with regard to these Þ gures, because of the strong stigma associated with mental disorders in this country.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Sweden in 2009 found mental disorders to predict malnutrition in community [9], whereas a German study conducted in the same year found no significant difference in mean malnutrition score between people with or without mental disorders [10]. Prevalence of mental illness varies from 6.5% to 31% among adults in Bangladesh [11]. According to national mental health survey conducted in 2003-2005, about 16.05% of the adult population has been suffering from mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Both urban and rural groups possess a higher vulnerability of mental illness among women compared to men [13]. Prevalence of mental illness among women are even higher among economically disadvantaged group and in rural areas [11,14]. Several studies have been identified comparing nutritional status of women from urban and rural areas in Bangladesh [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…If I focus on mental health services only, as I am considering that the closest health care support for people with sexual performance anxieties, it is in no way possible to address such a health problem. In a system review on mental disorders in Bangladesh, Hossain et al (2014) show that only 16% of the total number of people with mental disorders seek mental health support from the mental health professionals. Like the other health support, Bangladeshi people rely highly on traditional healing (Giasuddin et al, 2012;Islam et al, 2009 have negligible options outside of the informal system.…”
Section: The Traditional Healing System In Bangladesh and The Coloniamentioning
confidence: 99%